Affect theory as a tool: The work of Jordi Gal. Issue 161 (1st March 2014) - Pujol, Quim
This article explores the idiosyncrasy that lies behind the performances of Jordi Galí. It analyzes statements made by the artist in an epistolary exchange with the author and draws comparisons with some key concepts in the field of affect theory. It concludes that Galí's approach to performance is in accordance with many views put forward by affect theory, especially in relation to the blurring between object and subject. At the same time, it examines the mode of thinking and the political implications of affect theory in order to identify its main contributions and boundaries.